Implementasi Sak Emkm Dalam Penyusunan Laporan Keuangan (Studi Kasus Pada UD Biyanta Sokasi Desa Tigawasa) - Kadek Indra Dwi Priyanto; Made Arie Wahyuni (Universitas Pendidikan Ganesha, 2021)
Understand the financial reporting compiled in UD UMKM. Byanta Sokasi is the aim of the following research which must be adjusted to the Financial Accounting Standards for Micro, Small, and Medium Entities (SAK EMKM). The use of descriptive qualitative techniques is applied to the following research, in which the researching person conducts direct field observations and collects data on the things to be analyzed based on the monitoring and what the researcher knows. The research activity was held at UD Biyanta Sokasi which is located in Tigawasa Village, Banjar District, Buleleng Regency. Sources of data in this study include secondary data and primary data. Direct observation, interviewing, and documentation were chosen as the methods of collecting data for this research. A data analyzer is used which includes data reduction, presenting data, and analyzing data and then drawing conclusions.The research findings found that UD Biyanta Sokasi in the middle of making financial reports did not implement SAK EMKM. This is because the owners do not understand accounting and the owners think that the simple recording they do is enough and most importantly they can understand the records they make even though they do not match the rules and regulations that apply.